Development of Worksheet based on Elicit Confront Identify Resolve Reinforce (ECIRR) for Grade XI Science High School Students - Intan Zurma; Husna Husna; Rahmi Zulva (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
The curriculum 2013 requires students to be more active in the learning process. The case with physics learning carried out at SMA N 2 Batang Anai, it still focuses on learning from educators. Not only that, the use of teaching materials such as textbooks and worksheet has not been combined with learning models aimed at students, so that curriculum demands have not been achieved. One effort to overcome this is by developing elicit-based worksheets based on confront identify resolve reinforce for grade XI IPA students at SMA N 2 Batang Anai. The aim of the research is to produce valid and practical worksheet. The type of research used is Research and Development (RD), with the ASSURE model consisting of stages (1) recognizing the character of potential users of teaching materials, (2) determining the competence and learning objectives, (3) designing teaching materials, (4) producing teaching materials , (5) involving students in using teaching materials and (6) evaluating and revising teaching materials, this model is also combined with the Evalution Formative Tessmer which consists of expert review, one-to-one, small group and field test stages. The subjects of this study were 1 teacher and 40 students in grade XI IPA SMA N 2 Batang Anai. The results of the validity test show that the developed worksheet is categorized as very valid with a percentage of 94.15%. The value of practicality by educators and students shows that the worksheet developed is categorized as very practical with a proportion of 90.24%. Based on these results, the worksheet with material on dynamics of rotation and balance of rigid bodies that has been developed is categorized as valid and practical. After obtaining a valid and practical product, the product is suitable for use in assisting the learning process.